REFORMASI HUKUM PENYELESAIAN PERSELISIHAN HUBUNGAN INDUSTRIAL SECARA MEDIASI - Yetniwati Yetniwati; Hartati Hartati; Meriyani Meriyani (Jurnal Dinamika Hukum, 2014)
Dispute settlement of Industrial Relations through mediation stipulated in article 8 of the Act Number 2 Year 2004 was assisted by a mediator of manpower officials. In addition, article 9 regula-tes the qualifications of mediator. These two articles are very discriminatory as they are contrary to the fact that mediator of government officer should also be subject to the Civil Service Act. Besides, the government mediator would have superiors and subordinates according to the hierarchy of their positions. This would open possibility of intervention of the superiors that would interfere the mediator in performing his/her duties. Consequently, independent mediator would never be reali-zed. In fact, mediator is not only from government officer but also from other field such as lawyers, lecturers, National Commission of Human Rights (Komnas HAM), and any capable and non-allign-ed mediators. This would be one of solutions for the government to solve the shortage of mediators in Indonesia.                                                     Key words: mediation, mediator, law reform